An Analysis of Slang Words Used by Instagram Account Plesbol - Leo Saputra; Leni Marlina (Universitas Negeri Padang, 2019)
Slang is a language used by a specific group of people and usually used in an informal situation. Plesbol is an Instagram account that contained the various term of football and usually used slang words in its captions. This study aims to find out the types and the meaning of slang words used by Plesbol. This research used Elissa Mattiello’s theories (2008) about types of slang words. This study is descriptive qualitative research. The data were taken from captions of photos that have been uploaded by Plesbol from August until December 2018. The result showed that from 498 data that have been collected, there were nine types of slang that have been found from fifteen types of Elissa Mattiello’s slangs. They are acronym (16.15%), blending (27.43%), clipping (3.89%), compounding (27.71%), prefixation (0.13%), reduplicative (7.52%), reversed form (0.27%), variation (10.16%), and word manufacture and fanciful formation (6.68%). Compounding is the dominant slang with 27.71%. This finding of the study means more than fifty percent of Mattiello’s Slang words found in Plesbol.